T Cells Targeting SARS-CoV-2: By Infection, Vaccination, and Against Future Variants - Nguyen, Thi H. O.; Cohen, Carolyn A.; Rowntree, Louise C.; Bull, Maireid B.; Hachim, Asmaa; Kedzierska, Katherine; Valkenburg, Sophie A. (Frontiers in Medicine, 2021)
T cell responses are a key cornerstone to viral immunity to drive high-quality antibody responses, establishing memory for recall and for viral clearance. Inefficient recruitment of T cell responses plays a role in the development of severe COVID-19 and is also represented by reduced cellular responses in men, children, and diversity compared with other epitope-specific subsets and available T cell receptor diversity. SARS-CoV-2-specific T cell responses are elicited by multiple vaccine formats and augmented by prior infection for hybrid immunity. Epitope conservation is relatively well-maintained leading to T cell crossreactivity for variants of concern that have diminished serological responses.